O idadismo sob a escuta dos idosos: efeitos de sentido e a utopia de um novo envelhecer - Guides, Ana Carla Nogueira de Sousa (2016)
The new profile of the elderly, in this second decade of this century, brought greater visibility of old age, showing, however, one of its most intractable problems -the age social discrimination, manifested through speeches, conduct, and prejudiced gestures -still present in everyday interactions, from the Elder. The objective of this research is to investigate in the light of the perspective of Social Gerontology, the position of older people in episodes of age social discrimination and evaluate the resulting negative impact to them. It is based on a literature review, presenting some theoretical positions on prejudice and discrimination, subsumed in the term ageism (or ageism or Etarismo), and the interpretation of empirical data, answers to questions in an interview with the elderly. It is a qualitative, cross-sectional study with a sample of 14 subjects over 60 years of both sexes. There was filling out a sociodemographic questionnaire and a semi-structured interview, a closed question and some open, post-pilot project developed whose results appear in an article published. It is noteworthy that the results obtained there, and reiterated in the present investigation show, significantly, the presence of bias in all the variables applied. The effects of meaning to the subjects as varied affectation, confirming the unique character of each elderly person. The results suggest necessary actions to education about aging and the problems of old age, so that people of all age levels of society will realize that may have been prejudiced, even without realizing that thoughtless gesture. In short, that older people, especially the underprivileged, no longer receive the effects of age discrimination and may, having preserved their subjectivity, their work value, to live with dignity, with opportunities, contributing up in this way, to an improvement in intergenerational relationships in society. And becoming friendly, compassionate, appropriate for all ages, with the proposal of a citizen education -Happy utopia of a new age